Islamic Boarding School Leadership Strategy in Strengthening the Religious Character of Students in Darul Ihsan Islamic Boarding Schools of Aceh Besar - Nurhaliza, Siti; Ismail, Ismail; Khairuddin, Khairuddin; Zakaria, Nurhijrah Binti (Universitas Muhammadiyah Magelang, 2024)
This research aims to analyze leadership strategies of Darul Ihsan Islamic Boarding School in Aceh Besar in term of students’ religious character strengthening. The main issue faced is the lack of religious character strengthening for the students to face modern challenges. The research method used is qualitative descriptive with research subject that consists of boarding school’s head, teaching staff, and students. The data were collected by observation, in-depth-interview, and document analyses. The result of the research shows that the strategies implemented are including routine worshiping, habituation, exemplary, advice, and reward and punishment system. The strategies are proven to be effective in strengthening religious character of the students although there are several obstacles like change resistance and limited resources. The research concludes that structured and comprehensive leadership can improve students’ religious character significantly. However, it still requires evaluation and sustainable adjustment to encounter the obstacles.